2007
DOI: 10.1073/pnas.0702023104
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CNS synapses by neuronal MHC class I

Abstract: Until recently, neurons in the healthy brain were considered immune-privileged because they did not appear to express MHC class I (MHCI). However, MHCI mRNA was found to be regulated by neural activity in the developing visual system and has been detected in other regions of the uninjured brain. Here we show that MHCI regulates aspects of synaptic function in response to activity. MHCI protein is colocalized postsynaptically with PSD-95 in dendrites of hippocampal neurons. In vitro, whole-cell recordings of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
267
6
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(301 citation statements)
references
References 55 publications
16
267
6
5
Order By: Relevance
“…However, over the past decade, class I Mhc molecules have been implicated in the refinement of synapse formation and plasticity in the visual system and the hippocampus (Corriveau et al, 1998;Huh et al, 2000;Boulanger and Shatz, 2004) and in the maintenance of synapses of motoneurons (Oliveira et al, 2004). Mhc molecules are localized postsynaptically in dendrites of hippocampal neurons and appear to be involved in homeostatic regulation of synaptic function and morphology in response to neural activity (Goddard et al, 2007). A candidate Mhc class I receptor is expressed in subsets of neurons throughout the brain (Syken et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past decade, class I Mhc molecules have been implicated in the refinement of synapse formation and plasticity in the visual system and the hippocampus (Corriveau et al, 1998;Huh et al, 2000;Boulanger and Shatz, 2004) and in the maintenance of synapses of motoneurons (Oliveira et al, 2004). Mhc molecules are localized postsynaptically in dendrites of hippocampal neurons and appear to be involved in homeostatic regulation of synaptic function and morphology in response to neural activity (Goddard et al, 2007). A candidate Mhc class I receptor is expressed in subsets of neurons throughout the brain (Syken et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed that this mechanism underlies the injury of demyelinated axons in multiple sclerosis (MS) 1, 2, 4, 10. Evidence also suggests that MHC I is involved with synaptic pruning during cortical development12, 13, 14, 16, 17, 18, 19, 20, 21 and following injury22, 23, 24, 25 and contributes to neuronal plasticity 16, 17, 26, 27. These findings also suggest that retrogradely induced MHC class I may contribute to the diffuse synaptopathy observed in MS and other neurodegenerative diseases 28, 29, 30, 31, 32, 33, 34, 35.…”
Section: Introductionmentioning
confidence: 99%
“…It was not previously known which of the more than 50 MHCI family members might contribute to neuronal phenotypes observed in ␤2m Ϫ/Ϫ and/or ␤2m Ϫ/Ϫ TAP1 Ϫ/Ϫ mice (4,7,8,12). The fact that this large family of molecules is highly polymorphic in natural populations (1,2), and that the expression pattern of individual family members varies throughout the CNS (4), raises the intriguing possibility that particular MHCI molecules, as well as cognate receptors, may play specific roles in regulating the capacity of distinct brain circuits to change with learning and experience.…”
Section: Immune Compromise Cannot Account For Improved Motor Learningmentioning
confidence: 99%
“…Initial efforts to explore the function of MHCI in the CNS and olfactory bulb used ␤2m-and/or TAP1-deficient mice, which have markedly reduced cell surface expression of many, if not all, MHCI molecules (10,11). These studies implicate neuronal MHCI in activity-dependent synaptic plasticity in visual and hippocampal circuits (4,8). Additional studies of ␤2m Ϫ/Ϫ mice have revealed that the stability of inhibitory synapses onto spinal motor neurons is altered after axotomy (12), and these mice also have defects in pheromone receptor localization and male-male aggressive behavior (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation